THE FORMATION OF THE OIL AND GAS INDUSTRY IN THE CONTEXT OF WORLD EVENTS OF THE XX CENTURY - Mokrova E.M. (Вестник Брянского государственного университета)
The article retrospectively considers oil development history starting from the first use of the «black gold» in prehistoric times, first oil well drilling and ending with the oil industry development on the international level In the XX century. The author analyzes the correlation of human historic development and diversification of hydrocarbonic fuel usage. The article studies activities of the major oil corporations such as «Standard Oil», «Anglo-Persian Oil Company», as well as oil companies active at present – «Royal Dutch Shell», «British Petroleum», «Agip», etc. The impact of such pivotal events in the world history as Russian 1917 Revolution, WWI, WWII, post-WWII decolonization process and etc. on oil and gas market is examined. Complex interdependence of world historical events and oil production development is studied in the research. Comparative analysis of these developments and mutual impact of events is provided. Oil is considered as both a strategic fuel and an instrument of foreign policy.